2017
DOI: 10.1016/j.exer.2016.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and mechanotransduction in outflow pathway cells

Abstract: Because of elevations in IOP and other forces, cells in the trabecular meshwork (TM) are constantly subjected to mechanical strain. In order to preserve cellular function and regain homeostasis, cells must sense and adapt to these morphological changes. We and others have already shown that mechanical stress can trigger a broad range of responses in TM cells; however, very little is known about the strategies that TM cells use to respond to this stress, so they can adapt and survive. Autophagy, a lysosomal deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 70 publications
(105 reference statements)
1
47
0
Order By: Relevance
“…Strain causes profound changes to cell morphology, affecting motility, stiffness, contraction, orientation, and cell alignment (14-16). Recent studies have indicated autophagy as one of the relevant stress response adaptive mechanisms (16, 18, 19). Other genes that are impacted by the mechanical strain include those involved in extracellular matrix synthesis/remodeling, cytoskeletal organization, and cell adhesion (16, 20-25).…”
Section: Introductionmentioning
confidence: 99%
“…Strain causes profound changes to cell morphology, affecting motility, stiffness, contraction, orientation, and cell alignment (14-16). Recent studies have indicated autophagy as one of the relevant stress response adaptive mechanisms (16, 18, 19). Other genes that are impacted by the mechanical strain include those involved in extracellular matrix synthesis/remodeling, cytoskeletal organization, and cell adhesion (16, 20-25).…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is also activated in TM cells exposed to biaxial mechanical stretch and high pressure in a mTOR and BAG3 independent manner; interestingly, cyclic, but not static, mechanical stimulation of TM cells seems to activate a chaperone-assisted selective autophagy (CASA) (Hirt and Liton, 2017), a selective tension-induced autophagy previously described in muscle (Ulbricht et al, 2013).…”
Section: Trabecular Meshwork Autophagic Deregulation In Glaucomamentioning
confidence: 79%
“…Multiple genetic and molecular studies indicate the important contribution of autophagy to the pathogenesis of POAG (Frost et al, 2014; Hirt and Liton, 2017; Liton, 2016; Minegishi et al, 2016; Porter et al, 2015; Porter et al, 2013; Porter et al, 2014; Slowicka et al, 2016; Tucker et al, 2014; Wong and Holzbaur, 2014). As discussed earlier, a number of genetic factors are involved in or associated with the pathogenesis of POAG.…”
Section: Association Studies In Poagmentioning
confidence: 99%